Towards Green Energy: Assessing Biomass Densification Technologies for Power Generation - A.K Sharma; Pragya Yadav (International Journal of Energy and Thermal Applications, 2024)
Technologies for biomass densification have become essential for improving the profitability and efficiency of biomass-based energy production. This thorough review article examines several biomass densification-related topics, such as the technologies involved, process variables, benefits, difficulties, and possible uses. We explore the basic ideas behind biomass densification, including torrefaction, briquetting, and palletization, and we talk about the factors that affect their efficacy as well as their mechanisms. Furthermore, we examine the economic and environmental effects of biomass densification, emphasizing its contribution to the reduction of greenhouse gas emissions and the promotion of sustainable energy practices. This review aims to provide important insights into the development and application of biomass densification technologies for energy production by synthesizing recent research findings and technological advancements.
Keywords: Biomass densification; Pelletization; energy; production; sustainable